Meningkatkan Vocabulary Bahasa Inggris Dengan Menggunakan Puzzle Di Sekolah Dasar Buah Hati - Asma Alhusna; Noni Febriana; Dian Anggraini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Community Service (PKM) is a form of the Tridharma of Higher Education. This PKM is proposed to carry out activities that are outreach and educational in nature at Buah Hati Elementary School in Padang, West Sumatra Province. This activity is expected to help students improve their English Vocabulary by using Puzzles. Puzzle is a learning method that can improve students' English Vocabulary. In learning English, learning by using this puzzle is very helpful in increasing students' vocabulary in learning English. Because in the implementation of learning, students are trained to arrange several letters to become an English word. The purpose of this service is expected to be able to describe learning planning, increasing learning activities and increasing English Vocabulary using Puzzles. The method of implementing this service is carried out in several activities, namely the survey stage, namely by compiling various things that will be conveyed during the service activities to be carried out which include: preparation of the material to be given, preparation of the schedule for giving the material, division of tasks for the service team and surveys to the service location. The next stage, namely before the service activities are carried out, the socialization stage is carried out first, namely conducting friendship with the school principal, conveying the aims and objectives of this service. At this stage, collaboration is also carried out and determines the schedule of community service activities.